Rapid superparamagnetic‐beads‐based automated immunoseparation of Zn‐proteins from Staphylococcus aureus with nanogram yield. Issue 2 (12th December 2012) - Krizkova, Sona; Jilkova, Eva; Krejcova, Ludmila; Cernei, Natalia; Hynek, David; Ruttkay‐Nedecky, Branislav; Sochor, Jiri; Kynicky, Jindrich; Adam, Vojtech; Kizek, Rene
<x xml:space="preserve">Abstract</x> Pathogenic bacteria have become a serious socio‐economic concern. Immunomagnetic separation‐based methods create new possibilities for rapidly recognizing many of these pathogens. The aim of this study was to use superparamagnetic particles‐based fully automated instrumentation to isolate pathogen Staphylococcus aureus and its Zn(II) containing proteins (Zn‐proteins). The isolated bacteria were immediately purified and disintegrated prior to immunoextraction of Zn‐proteins by superparamagnetic beads modified with chicken anti‐Zn(II) antibody. S. aureus culture was treated with ZnCl2. Optimal pathogen isolation and subsequent disintegration assay steps were carried out with minimal handling. (i) Optimization of bacteria capturing: Superparamagnetic microparticles composed of human IgG were used as the binding surface for acquiring live S. aureus. The effect of antibodies concentration, ionic strength, and incubation time was concurrently investigated. (ii) Optimization of zinc proteins isolation: pure and intact bacteria isolated by the optimized method were sonicated. The extracts obtained were subsequently analyzed using superparamagnetic particles modified with chicken antibody against zinc(II) ions. (iii) Moreover, various types of bacterial zinc(II) proteins precipitations from particle–surface interactions were tested and associated protein profiles were identified using SDS‐PAGE. Use of a robotic pipetting system sped up sample preparation to less than 4 h. Cell lysis and Zn‐protein extractions were obtained from a minimum of 100 cells with sufficient yield for SDS‐PAGE (tens ng of proteins). Zn(II) content and cell count in the extracts increased exponentially. Furthermore, Zn(II) and proteins balances were determined in cell lysate, extract, and retentate.